2019
DOI: 10.1242/jeb.187005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the maternal and current social environment on female body mass and reproductive traits in Japanese quail (Coturnix japonica)

Abstract: The social environment of breeding females can affect their phenotype, with potential adaptive maternal effects on offspring that experience a similar environment. We housed Japanese quail (Coturnix japonica) females in two group sizes (pairs versus groups of four) and studied the effects on their offspring under matched and mismatched conditions. We measured F1 body mass, reproduction, and plasma levels of androgens and corticosterone. F1 group housing led to an increase in body mass. In addition, F1 group ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…There are fewer data on intergenerational social stressors in non-mammals; in birds, the effects of maternal social stress on offspring stress physiology and behaviour are inconclusive. For example, Langen et al (2019) showed that in Japanese quail ( Coturnix japonica ), maternal group size has no effect on offspring glucocorticoid response, whereas in gulls ( Larus fuscus ), parental density affects offspring social behaviour ( Salas et al, 2022 ). Furthermore, zebra finch offspring from parents where mothers experienced pair separation and re-pairing are less behaviourally responsive to isolation (vocalisations and perch hops: Schweitzer et al, 2014 ), and, in quail, maternal social instability increases offspring emotional reactivity (e.g.…”
Section: Social Stress Across the Lifespanmentioning
confidence: 99%
“…There are fewer data on intergenerational social stressors in non-mammals; in birds, the effects of maternal social stress on offspring stress physiology and behaviour are inconclusive. For example, Langen et al (2019) showed that in Japanese quail ( Coturnix japonica ), maternal group size has no effect on offspring glucocorticoid response, whereas in gulls ( Larus fuscus ), parental density affects offspring social behaviour ( Salas et al, 2022 ). Furthermore, zebra finch offspring from parents where mothers experienced pair separation and re-pairing are less behaviourally responsive to isolation (vocalisations and perch hops: Schweitzer et al, 2014 ), and, in quail, maternal social instability increases offspring emotional reactivity (e.g.…”
Section: Social Stress Across the Lifespanmentioning
confidence: 99%
“…Environmental parental effects, also known as transgenerational plasticity, are widespread in plants and animals (Bell & Hellmann, 2019; De Long et al, 2021; Donohue, 2009; Herman & Sultan, 2011; Meaney, 2001; Roach & Wulff, 1987; Rossiter, 1991; Weaver et al, 2004). Transgenerational plasticity has been demonstrated in response to a wide variety of ecological factors: temperature (Betini et al, 2020; Landy & Travis, 2018; Lee et al, 2020; Penney et al, 2021; Salinas & Munch, 2012; Sun et al, 2018; Tougeron et al, 2020), salinity (Griffiths et al, 2021), food availability (Kangassalo et al, 2020; Plaistow et al, 2006; Vega‐Trejo et al, 2018), exposure to predation risk (Hellmann et al, 2020; Lehto & Tinghitella, 2020; McGhee et al, 2021; Tariel et al, 2020), herbivory (Sobral, Sampedro, et al, 2021), and conspecific density (Langen et al, 2019; Li et al, 2019; Meise et al, 2016). However, the extent to which these effects represent adaptive plasticity between parent and offspring generations remains contentious (Marshall & Uller, 2007; Sanchez‐Tojar et al, 2020; Uller et al, 2013; Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are compelling examples of adaptive plasticity (Allen et al, 2008; Galloway & Etterson, 2007; Kangassalo et al, 2020; Sun et al, 2018; Tougeron et al, 2020). However, many studies have either failed to find transgenerational plasticity where it was expected or found it to be maladaptive (Betini et al, 2020; Griffiths et al, 2021; Langen et al, 2019; Martin et al, 2019; Neylan et al, 2022; Penney et al, 2021). For any single ecological agent like conspecific density, some experiments demonstrate an adaptive effect (Langen et al, 2019) while others do not (Zipple et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A situation in which there can be far-ranging inter-and transgenerational effects arises when a female's state affects her reproductive decisions or investment. This can shape various aspects of the life-history and reproductive strategy of her offspring (the F1 generation) [19][20][21]. These in turn can influence the development, survival and reproductive success of her grandoffspring (the F2 generation).…”
Section: Introductionmentioning
confidence: 99%